The effects of integrated pest management program on productivity and income of rice farmers in selected barangays of Bontoc, Southern Leyte - Sescon, Martha B.
This study documents and analyzes the effects of the Farmer Field School (FFS) on Integrated Pest Management (IPM) Kasaganahan ng Sakahan at Kalikasan (Kasakalikasan) Program on productivity and income of rice farmers n selected barangays of Bontoc. Southern Leyte. The sustainability of the IPM approaches on the farmers' farming activities within a barangay and the empowerment of farmers when it comes to decision-making as farm manager are concerns that were addressed in the study. Barangays Cawaayanan, Divisoria, Mauylab and San Vicente are the recipient of the Season-Long Farmer Field School on Integrated pest Management training in the municipality of Bontoc.This study used purposive sampling. Forty percent of the total number of the training beneficiaries were taken as respondents. Out of 100 farmer 40 were randomly selected. An interview schedule was formulated in English but wastranslated to Cebuano dialect for easy comprehension on the part of the respondents. The data were consolidated and analyzed using descriptive statistics in the form of frequency distribution, range and percentages. The findings of the study reveal a positive effects of FFS-IPM Program both for pre-planting and planting operation, farmers' productivity on income, and its effectiveness and sustainability to the respondents farming practices. Sixty percent of the respondents implemented the program for 6 to 10 years and forty percent from 1 to 5 years since the inception of the above-mentioned program in the recipient barangays.